DETECTION OF BACTERIAL PATHOGENS IN PADDY SEED LOTS IN PAKISTAN (Biological Sciences - PJSIR, 2022)
One hundred and fifty three seed samples were collected from major paddy crop growing areas during 1987-88 to1990-91 and tested for the presence of seed-borne bacterial pathogens using a seedling symptom test. Maximum seedinfection due usXanthomonas oryzae pv. oryzae, ex Ishiyama (Swings eta!.) was II and 12% in variety IRRI-6 at Lahoreand Hyderabad respectively. While in case of Acidovorax avenae sub sp. avenae, infection was 13% in variety B-385from Sahiwal. It was observed that the percentage of seed infection due to bacterial pathogens varied from cultivar tocultivar in different localities. Keeping in veiw the high infection level of these bacterial diseases, future studies areneeded on seed transmission and epidemiology of these pathogens for better disease control strategies.